Potencial del turismo gastronómico del cantón Pujilí de la provincia de Cotopaxi. - Ante Tulpa, Alex Edison (2023)
The objective of this work was to evaluate the potential of gastronomic tourism in the Pujilí canton of the Cotopaxi province. Where three specific objectives were raised: knowing the potential of gastronomic tourism in the Pujilí canton, identifying the current market and potential / potential of gastronomic tourism and preparing proposals for an academic article as a means of disseminating research in the RENPYS magazine. For this, in the first objective, it has been proposed to use the SIGAP 2015 methodology, where it was possible to determine the current situation of the study site, resulting in Pujilí having 7 parishes each with natural and cultural attractions, the main economic activities are agriculture, livestock and handicrafts, for the current and potential market, it was identified that tourist activities exist in the canton related to tourism, then the existing tourist plant in the Pujilí canton was determined, the methodology for the elaboration of a gastro tourist map was applied. MINTUR economic report with the four criteria to be evaluated; history and tradition, local ingredients, current tradition, offer at the destination, linked to the SIGAP 2015 traffic light methodology, where a score of 75 to 100 was obtained to qualify the 18 representative dishes of the research site, which are: corn tortilla, guinea pig with potatoes, fried, black pudding, chaguarmishqui, tamales, baked, Creole chicken water, Creole chicken dry, sancocho, quinoa with oreja de chan cho, runaucho, roast lamb, cassava with fish, tripe broth, cooked potatoes, mellocos, broad beans and ocas, barley rice with milk and brown sugar, guinea pig locro, guinea pig with potatoes, which meet the four aforementioned criteria, therefore it was concluded that the canton has a high potential for gastronomic tourism.